The Elves and the Shoemaker - Daynes, Katie; Guicciardini, Desideria (London Usborne House, 2004)
The Elves and the Shoemaker is in Series One of Usborne Young Reading, which combines good stories with easy reading text. Usborne Young Reading has been developed in consultation with Alison Kelly, Senior Lecturer at Roehampton University. Series One is for readers who have just started reading alone.
Location: 3A
Keywords: Fiction